Managing critical care during COVID-19 pandemic: The experience of an ICU of a tertiary care hospital. Issue 11 (November 2021) - Al-Dorzi, Hasan M.; Aldawood, Abdulaziz S.; Almatrood, Amal; Burrows, Victoria; Naidu, Brintha; Alchin, John D.; Alhumedi, Haifaa; Tashkandi, Nabeeha; Al-Jahdali, Hamdan; Hussain, Arif; Al Harbi, Mohammed K.; Al Zaibag, Muayed; et al.
Abstract: Background: The COVID-19 pandemic has strained ICUs worldwide. To learn from our experience, we described the critical care response to the outbreak. Methods: This is a case study of the response of the Intensive Care Department (75-bed capacity) at a tertiary-care hospital to COVID-19 pandemic, which resulted in a high number of critically ill patients. Results: Between March 1 and July 31, 2020, 822 patients were admitted to the adult non-cardiac ICUs with suspected (72%)/confirmed (38%) COVID-19. At the peak of the surge, 125 critically ill patients with COVID-19 were managed on single day. To accommodate these numbers, the bed capacity of 4 ICUs was increased internally from 58 to 71 beds (+40%) by cohorting 2 patients/room in selected rooms; forty additional ICUs beds were created in 2 general wards; one cardiac ICU was converted to managed non-COVID-19 general ICU patients and one ward was used as a stepdown for COVID-19 patients. To manage respiratory failure, 53 new ICU ventilators, 90 helmets for non-invasive ventilation and 47 high-flow nasal cannula machines were added to the existing capacity. Dedicated medical teams cared for the COVID-19 patients to prevent cross-contamination. The nurse-to-patient and RT-to-patient ratio remained mostly 1:1 and 1:6, respectively. One-hundred-ten ward nurses were up-skilled to care for COVID-19 and other ICU patients using tiered staffing model. Daily executive rounds were conducted to identify patients for transfer and at least 10 beds were made available for new COVID-19 admissions/day. The consumption of PPE increased multiple fold compared with the period preceding the pandemic. Regular family visits were not allowed and families were updated daily by videoconferencing and phone calls. Conclusions: Our ICU response to the COVID-19 pandemic required almost doubling ICU bed capacity and changing multiple aspects of ICU workflow to be able to care for high numbers of affected patients.